Impacts of Future NO_x and CO Emissions on Regional Chemistry and Climate over Eastern China - 王革丽 杨培才 刘传熙 刘毅 吕达仁 (Advances in atmospheric sciences, 2010)
A coupled chemical/dynamical model （SOCOL-SOlar Climate Ozone Links） is applied to study the impacts of future enhanced CO and NO_x emissions over eastern China on regional chemistry and climate. The result shows that the increase of CO and NOx emissions has significant effects on regional chemistry, including NOx, CO, O_3, and OH concentrations. During winter, the CO concentration is uniformly increased in the northern hemisphere by about 10 ppbv. During summer, the increase of CO has a regional distribution. The change in O_3 concentrations near eastern China has both strong seasonal and spatial variations. During winter, the surface O_3 concentrations decrease by about 2 ppbv, while during summer they increase by about 2 ppbv in eastern China. The changes of CO, NO_x, and O_3 induce important impacts on OH concentrations. The changes in chemistry, especially O_3, induce important effects on regional climate. The analysis suggests that during winter, the surface temperature decreases and air pressure increases in central-eastern China. The changes of temperature and pressure produce decreases in vertical velocity. We should mention that the model resolution is coarse, and the calculated concentrations are generally underestimated when they are compared to measured results. However, because this model is a coupled dynamical/chemical model, it can provide some useful insights regarding the climate impacts due to changes in air pollutant emissions.